Discourse framework and reshaping path of British media report on Chinese Confucius Institutes - Leiya Tian (Ilmu Inovasi Nusantara, 2025)
The historical differences between China and Western countries and the dominant discourse of Western media have led to doubts and biases in international public opinion regarding the reporting of Confucius Institutes. The British media serves as a typical example of shaping this negative perception. This study aims to analyze how major British media outlets frame reports on Confucius Institutes using the theory of framing analysis. Through an examination of seven major news media in the United Kingdom, the study finds that reporting on Confucius Institutes is primarily framed within three core themes: the